Exegetic homilies - Basil, Saint, Bishop of Caesarea, approximately 329-379 (Fathers of the church, 1963)
Contains nine homilies on the Hexaemeron, and one each on Psalm 1, 7, 14, 28, 29, 32, 33, 44, 45, 48, 59, 61, and 114.